1968
DOI: 10.1021/ja01006a003
|View full text |Cite
|
Sign up to set email alerts
|

Ion cyclotron resonance study of ion-molecule reactions in methanol

Abstract: A branching chain mechanism is observed in the methanol ion-molecule system which involves complex formation and collisional stabilization of complex ions. A protonated methanol ion CH3OH2+ is the main product of the reactions of primary ions present. Collisions of this ion with methanol lead to complex ions (CH3OH)"H + at high pressure. At lower pressure, in the absence of collisional stabilization, a protonated dimethyl ether ion (CH3)2OH+ is produced. The structure of the (CH3)2OH+ ion was verified, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

1969
1969
2007
2007

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(38 citation statements)
references
References 2 publications
2
36
0
Order By: Relevance
“…The reaction of methanol to [CH 3 ] 2 OH ϩ has been previously observed as the dominant fragmentation product generated in a potential field of 70 V and a 50 m path at 10 Ϫ5 torr [43]. In this earlier study, the identity of this species has been confirmed as the protonated dimethyl ether ion, hypothesized to be a product of the protonated methanol dimer.…”
Section: Generation Of Solvent Ions In Methanol Vaporsupporting
confidence: 51%
“…The reaction of methanol to [CH 3 ] 2 OH ϩ has been previously observed as the dominant fragmentation product generated in a potential field of 70 V and a 50 m path at 10 Ϫ5 torr [43]. In this earlier study, the identity of this species has been confirmed as the protonated dimethyl ether ion, hypothesized to be a product of the protonated methanol dimer.…”
Section: Generation Of Solvent Ions In Methanol Vaporsupporting
confidence: 51%
“…We therefore conclude that the structure of the ion at m/z 47 in the mass spectra of methanol is protonated dimethyl ether. This agrees with the results reported by Henis in 1968 [21].…”
Section: Resultssupporting
confidence: 94%
“…techniques employed here, except for ion ejection double resonance (9), were those described by Henis (19). Our ionizing current was 0.05 PA; total ion current, < 10 PA; typical cell voltages were: trap, 0.48 V; analyzer, split (20) From the optical absorption spectrum observed by a sub-nanosecond pulse radiolysis method it is concluded that irradiated pure liquid formamide (dielectric constant = 109) does not yield solvated electrons with lifetimes > lo-'' s. In formamide-water mixtures the hydrated electron is formed in low yield and the position of the absorption band of e,,-is not altered by changing the composition.…”
Section: Methodsmentioning
confidence: 99%